PARTISIPASI PEMILIH PADA PEMILIHAN UMUM PRESIDEN DAN WAKIL PRESIDEN TAHUN 2019 DI KOTA PEKANBARU - Febri Kurniawan; Zaili Rusli SD (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Voter Participation in the General Election of the President and Vice President which is held within 5 years is a democracy party in Indonesia and in 2019 it is different from the previous elections, because in 2019 it was held simultaneously at the same time as the Legislative election. As well as ethnic, racial, ethnic and religious religions in Pekanbaru City is the main thing which in the future to see interest in participation for voters is a phenomenon that is found. The purpose of this study is to determine how voter participation in the 2019 presidential and vice presidential elections in Pekanbaru City and to determine the inhibiting factors for voter participation in the 2019 Presidential and Vice-Presidential elections in Pekanbaru City. This study used purposive sampling technique with qualitative research using a phenomenological approach and the required data, both primary and secondary data, were obtained through observation, interviews and documentation and then analyzed based on the research problem. The results of this study indicate that: High voter participation is accompanied by an active response from the community in the campaign process, discussion of the vision and mission of the presidential candidate pairs to the community or their closest circle. The factors inhibiting voter participation in the 2019 presidential and vice presidential elections in Pekanbaru city are the mindset of the community, socialization, busy daily activities, and social media.              Keywords: Participation, Voters, General Elections